Direct, large area growth of few-layered MoS2 nanostructures on various flexible substrates: growth kinetics and its effect on photodetection studies. (25th January 2018) - Sahatiya, Parikshit; Jones, S Solomon; Badhulika, Sushmee
Abstract: Even though the chemical vapor deposition approach for synthesizing MoS2 has gained in importance, direct large area growth of MoS2 on flexible substrates remains a challenge. The synthesis of MoS2 has mostly been performed in a vacuum or by thermolysis, requiring elevated temperatures and intricate post-processing techniques. Ease of synthesis of MoS2 on different flexible substrates, using a solution process strategy, would make the potential applications of MoS2 in electronics, optoelectronics and energy storage more viable. In this work we report for the first time the one-step solution-processed growth of MoS2 on various flexible substrates (cellulose paper, Al foil, Cu foil, polyimide, carbon paper, ceramic paper and cotton thread). The growth kinetics of MoS2 is explained in terms of surface energies of substrates and classical theory of nucleation and growth. The growth of MoS2 on these substrates not only yielded different morphologies of MoS2 nanosheets, but also the layers of MoS2 varied, thus confirming the key role of the substrate during the growth process. Finally, photodetection studies performed on MoS2 grown on the flexible substrates suggest that defects introduced during the hydrothermal process play a crucial role in the performance of the photodetector. This study paves the way for simple, large area solution-processed synthesis of MoS2 on various arbitrary substrates, with potential applications in the fields of optoelectronics, medical and energy storage, etc.